Tele-Education in South Africa - Mars, Maurice (Frontiers in Public Health, 2014)
Introduction: Telemedicine includes the use of information and communication technology for education in the health sector, tele-education. Sub-Saharan Africa has an extreme shortage of health professionals and as a result, doctors to teach doctors and students. Tele-education has the potential to provide access to education both formal and continuing medical education. While the uptake of telemedicine in Africa is low, there are a number of successful and sustained tele-education programs. The aims of this study were (i) to review the literature on tele-education in South Africa, (ii) describe tele-education activities at the University of KwaZulu-Natal (UKZ-N) in South Africa, and (iii) review the development of these programs with respect to current thinking on eHealth project implementation. Method: A literature review of tele-education in South Africa was undertaken. The development of the tele-education services at UKZ-N from 2001 to present is described. The approaches taken are compared with current teaching on eHealth implementation and a retrospective design-reality gap analysis is made. Results: Tele-education has been in use in South Africa since the 1970s. Several forms of tele-education are in place at the medical schools and in some Provincial Departments of Health (DOH). Despite initial attempts by the National DOH, there are no national initiatives in tele-education. At UKZ-N, a tele-education service has been running since 2001 and appears to be sustainable and reaching maturity, with over 1,400 h of videoconferenced education offered per year. The service has expanded to offer videoconferenced education into Africa using different ways of delivering tele-education. Conclusion: Tele-education has been used in different forms for many years in the health sector in South Africa. There is little hard evidence of its educational merit or economic worth. What it apparent is that it improves access to education and training in resource constrained settings. The development of local and international tele-education at the UKZ-N has not followed what is currently considered to be best practice but shows how programs can develop if there is a real need and the solution assists in meeting the need. Further work is required to analyze the economics of these tele-education endeavors.